THE USE OF DEIXIS IN THE FORMS OF SENTENCES IN THE NOVELLA “OF MICE AND MEN” BY JOHN STEINBECK - Chandrakusuma, Yayang; Rosmiati (Faculty of Letters Universitas Balikpapan, 2026)
This research analyzes the use of deixis in the forms of sentences in the novella ‘Of Mice and Men’ by John Steinbeck. The purposes of this study are two: 1) to identify the types of deixis that appear in the novella, 2) to describe deixis used in within the novella. The research applies a descriptive qualitative. since the data are presented and analyzed in the form of words and utterances rather than numbers. The findings reveal five types of deixis used in the novella: person deixis, place deixis, time deixis, discourse deixis, and social deixis. In addition, the study shows the use of each deixis: person deixis has primary, social, referential and textual function. Place deixis has primary, psychological, and metaphorical function. Time deixis has primary, textual, and psychological function. Social deixis has primary, politeness, identity, and pragmatic function. Discourse has primary, cohesive, referential, and structuring function. From the 400 excerpts found by the researcher the most dominant are the primary function of person deixis with over 390 out of 400 excerpts, meanwhile the least dominant is pragmatic function of social deixis with over 1 out of 400 excerpts found by the researcher.